Crystal structure of a hedgehog autoprocessing domain: homology between hedgehog and self-splicing proteins. - Hall, T.M.T.; Porter, J.A.; Young, K.E.; Koonin, E.V.; Beachy, P.A.; Leahy, D.J. (Cell, 1997)
The approximately 25 kDa carboxy-terminal domain of Drosophila Hedgehog protein (Hh-C) possesses an autoprocessing activity that results in an intramolecular cleavage of full-length Hedgehog protein and covalent attachment of a cholesterol moiety to the newly generated amino-terminal fragment. We have identified a 17 kDa fragment of Hh-C (Hh-C17) active in the initiation of autoprocessing and report here its crystal structure. The Hh-C17 structure comprises two homologous subdomains that appear to have arisen from tandem duplication of a primordial gene. Residues in the Hh-C17 active site have been identified, and their role in Hedgehog autoprocessing probed by site-directed mutagenesis. Aspects of sequence, structure, and reaction mechanism are conserved between Hh-C17 and the self-splicing regions of inteins, permitting reconstruction of a plausible evolutionary history of Hh-C and the inteins.